The Influence of Knowledge-Driven Motivation, Economic Incentives, Self-Confidence, and Job Market Factors on Accounting Students' Interest in Pursuing a Career in Taxation - Vita Agustina; Lintang Kurniawati (Program Pascasarjana STIE Amkop Makassar, 2025)
This study aims to investigate the impact of knowledge motivation, economic motivation, self-efficacy, and labor market factors on the propensity of accounting students to pursue a career in taxation. A quantitative methodology was employed in this research, collecting primary data via questionnaires administered to undergraduate students at the University of Muhammadiyah Surakarta. A total of 111 respondents were analyzed using multiple linear regression techniques with SPSS software. The findings reveal that both knowledge motivation and economic motivation exert a statistically significant and positive influence on interest in taxation careers. In contrast, self-efficacy and labor market factors did not show a significant impact on student interest. An Adjusted R² value of 0.046 indicates that these four variables explain 4.6% of the variation in career interest, with the remainder attributed to other external factors.